Detection of Viral Haemorrhagic Septicemia in Marine Fisheries Commodity Using Real Time–PCR at Fish Quarantine Inspection Agency Denpasar, Bali - Fitriana, Evi; Kenconojati, Hapsari; Faizal Ulkhaq, Mohammad; Habib Fasya, Arif; Nurlita, Wahyu (Universitas Airlangga, 2024)
Marine fish commodities in Indonesia, both exported and imported, have experienced a significant increase. This increase opens up opportunities for the risk of entry and spread of fish pests and diseases, both on an export scale between countries and between areas within Indonesia. One of the pathogens that is acute that can cause major losses is the virus. The virus that often attacks sea water ornamental fish is Viral haemorrhagic septicemia. The purpose of this study was to detect the presence of VHSV that infects marine ornamental fish commodities using namely: necropsy, fixation, extraction, amplification, and reading of results. This research was conducted at Fish Quarantine Inspection Agency Denpasar, Bali. Based on the test results, VHS was found to attack six samples of marine fish species with codes namely NTC, BC 8.2, BC 9.2, BAR 8.2, 1252, NSR 8.2.